Risk Factors Associated With School Bullying Behaviors: A Chinese Adolescents Case-Control Study, 2019 - Qian, Yining (Journal of interpersonal violence, 2022)
This research aimed to identify risk factors including individual characteristics and environment circumstances related to different types of school bullying (physical, relational, verbal, sexual, and possession bullying) among middle school students in China. Cases were the respondents reporting perpetrating bullying behaviors three or more times in the past year. One control was selected for each case from those participants who were not involved in school bullying in the past 12 months. Data were collected between April 2019 and May 2019 in China. After considering potential confounding variables including gender, grade level, and school, multivariable conditional logistic regression analysis was performed based on the univariate logistic analysis including 1,594 adolescents. According to conditional logistic regression analysis, alcohol use and lack of emotional management and control were the significant individual characteristics positively associated with involvement in school bullying. Alcohol use was related to all five types of school bullying perpetration. Poor relationships between family members, father?s alcohol use, and parental neglect were strong risk factors for relational bullying. Lack of a sense of safety and absence of trusted people were associated with physical, relational, and verbal bullying perpetration. Results of this study provide evidence about risk factors for school bullying and have implications for potential policies to reduce bullying. Effective policies and programs need to take individual characteristics (social-emotional skills, anger control), family (parent training in conflict resolution, appropriate disciplining), peer and school factors (promoting prosocial networks, zero tolerance for bullying, appropriate disciplining policies against students who bully others, teacher training on building positive teacher?student relationships and positive discipling techniques) into consideration in order to develop effective prevention programs.